Association mapping to identify molecular markers associated with resistance genes to stink bugs in soybean - Ghione, Celina Elena; Lombardo, Lucio; Vicentin, Ignacio Gabriel; Heinz, Ruth Amelia (Springer, 2021)
Damage generated by insects is one of main restricting factors for soybean production. Stink bugs are a great threat within pests because, by feeding mainly on pods, they cause direct and irreversible damage to developing seeds. Thus, plant resistance is an important management strategy to reduce insect population impact on yield losses. Association mapping can be used as a powerful tool for dissecting resistance mechanisms in soybean, more specifically to recover functional loci involved in plant defense against herbivorous insects; and can also provide valuable markers for the development of soybean cultivars with resistance. The purpose of this study was to identify molecular markers associated with resistance genes to stink bugs in a collection of soybean germplasm, using the association mapping strategy. According to the decline value in the linkage disequilibrium, an accurate power of mapping resolution was predicted in this population. Four associated markers located in chromosomes 6 and 15 were identified. Out of the 112 candidate genes close to them, 31 would encode proteins related to defense pathways triggered by the attack of herbivorous insects. The proteins encoded by these candidate genes could be associated to the jasmonic acid pathway. The main contribution of this study was the identification of molecular markers associated with resistance genes to stink bugs. These markers will be a useful tool for marker-assisted selection applied to soybean genetic breeding.